2015
DOI: 10.1108/srj-04-2014-0056
|View full text |Cite
|
Sign up to set email alerts
|

Women as a stakeholder: a qualitative study in Turkey

Abstract: Purpose – This study aims to determine the efforts in the topic of women in the direction of corporate social responsibility (CSR) activities as one of the stakeholders of the companies. Design/methodology/approach – This study is based on a survey of what has been written on the topic of women and CSR in Turkey. The data obtained, and the methodology used, come from Web sites belonging to the top 50 of Turkey’s 500 Big Industrial Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Kori can and Jelavi c (2008) argued that although there were a number of women managers, they were still discriminated against by their male counterparts. Oruc (2015) found that women played a vital role as advocates for CSR not only at the directorship level of a firm but equally as important stakeholders of the business. Stakeholder theory also predicted that female directors on boards could improve the social performance of firms (Macaulay et al, 2018).…”
Section: Gender Diversity and Corporate Social Responsibilitymentioning
confidence: 99%
“…Kori can and Jelavi c (2008) argued that although there were a number of women managers, they were still discriminated against by their male counterparts. Oruc (2015) found that women played a vital role as advocates for CSR not only at the directorship level of a firm but equally as important stakeholders of the business. Stakeholder theory also predicted that female directors on boards could improve the social performance of firms (Macaulay et al, 2018).…”
Section: Gender Diversity and Corporate Social Responsibilitymentioning
confidence: 99%
“…In Indonesia, Mahy (2011) investigated how a mining corporation engaged in gender equality practices by using CSR as a tool per the guidelines by the World Bank, Rio Tinto and Oxfam Australia. Similarly, while trying to understand the role of females in society, and more specifically as stakeholders in corporations, a study conducted in Turkey by Oruc (2015) investigated the role of females as stakeholders in the top 50 industrial organisations (Hackston and Milne, 1996). Disclosures on websites and in sustainability reports showed that efforts are made to perceive females as stakeholders, but these efforts are limited.…”
Section: Literature Reviewmentioning
confidence: 99%